Comparing commercial and slow-growing broilers in Thailand: growth, carcass quality, economics, and environmental perspective - Panatda Bungsrisawat; Surasek Tunseng; Savek Kiatsomphob; Sombat Prasongsook; Chaiyapoom Bunchasak; Choawit Rakangthong (Poultry Science)
Various aspects were compared of commercial and slow-growing broiler chickens in Thailand. In total, 416 one-day-old chicks of a commercial strain (COM) and a slow-growing strain (SG) were assigned equally to four experimental groups separated by strain and sex with 8 replications per group, using a 2 × 2 factorial in a completely randomized design. All birds were fed according to the recommended diets for each strain and sex, with the endpoint of the study at a final body weight of 2.5 kg/bird for each group. Growth performance parameters were assessed, and a separate digestibility study was conducted to evaluate nutrient intake, excretion, and retention, with a focus on assessing environmental impacts. The COM strain groups had a highly significant greater growth rate with lower feed intake and a better feed conversion ratio compared to SG strain groups, while the mortality rate did not differ between groups. The COM strain had a higher breast muscle yield, whereas SG produced significantly higher amounts of thighs and drumsticks. Furthermore, the feed ingredient ratios for energy (corn), protein (soybean meal), and phosphorus were lower in COM than for SG. The COM male broiler group had a significantly higher nitrogen digestion rate, with lower intake and excretion of nitrogen and phosphorus compared to SG. Economically, the COM strain groups had a lower feed cost than SG strain groups by approximately 16 % compared to SG, while the feed cost of COM was lower by 8 % in males and 23 % in females than for the equivalent SG groups. The interaction of strain and sex was highly significant in carbon emissions. The COM male group had lower carbon emissions compared to COM female, SG male, and SG female groups, which were 5.17 %, 11.73 %, and 31.25 %, respectively. In conclusion, raising commercial broiler chickens appeared to be more sustainable, effective and economic with a better environmental impact than raising slow-growing broiler chickens. This study did not evaluate welfare indicators, which should be addressed in future research.